Improving Student Digital Literacy through Google Classroom-Based Lectures - Sadieda, Lisanul Uswah; Sutini, Sutini (Prodi Pendidikan Matematika FTIK IAIN Palopo, 2023)
Abstract:Mathematics teacher candidates need to have good digital literacy so that they will be able to guide their students to use digital media wisely. Therefore this study aims to describe the increase in students' digital literacy after attending microteaching lectures (Introduction to Schooling Field 1) using Google Classroom. This type of research is quasi-experimental research with a quantitative approach. The research sample was 30 students in the 6th semester of the 2021/2022 academic year. Methods of collecting data using performance tests. Data analysis of students' digital literacy improvement used the Wilcoxon Signed-Rank Test. Digital literacy indicators used include aspects of technical skills, critical understanding, and communicative abilities. Based on the analysis of research data, it is concluded that there is an increase in student digital literacy after attending lectures using Google Classroom. Student digital literacy is included in the advanced category.Abstrak:Mahasiswa calon guru matematika perlu memiliki literasi digital yang baik agar nantinya mampu membimbing peserta didiknya menggunakan media digital dengan bijak. Oleh karena itu penelitian ini bertujuan mendeskripsikan peningkatan literasi digital mahasiswa sesudah mengikuti perkuliahan microteaching (Pengenalan Lapangan Persekolahan 1) menggunakan Google Classroom. Jenis penelitian adalah penelitian eksperimen semu dengan pendekatan kuantitatif. Sampel penelitian adalah 30 mahasiswa semester 6 tahun akademik 2021/2022. Metode pengumpul data menggunakan tes unjuk kerja. Analisis data peningkatan literasi digital mahasiswa menggunakan uji Wilcoxon Signed-Rank Test. Indikator literasi digital yang digunakan meliputi aspek technical skill, critical understanding dan communicative abilities. Berdasarkan analisis data penelitian diperoleh simpulan bahwa terdapat peningkatan literasi digital mahasiswa setelah mengikuti perkuliahan menggunakan Google Classroom, Literasi digital mahasiswa termasuk dalam kategori advance.